2009
DOI: 10.1634/stemcells.2008-0439
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Pluripotent Human Spermatogonial Stem Cell-Derived Cells

Abstract: Several reports have documented the derivation of pluripotent cells (multipotent germline stem cells) from spermatogonial stem cells obtained from the adult mouse testis. These spermatogonia-derived stem cells express embryonic stem cell markers and differentiate to the three primary germ layers, as well as the germline. Data indicate that derivation may involve reprogramming of endogenous spermatogonia in culture. Here, we report the derivation of human multipotent germline stem cells (hMGSCs) from a testis b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
220
1
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(229 citation statements)
references
References 64 publications
(91 reference statements)
5
220
1
3
Order By: Relevance
“…Our research proved that ES-like cells originated from spermatogonia cells, express high ES-like cells have the same molecular profiling as embryonic stem cells (Mardanpour et al 2008;Kossack et al 2009). …”
Section: Discussionsupporting
confidence: 58%
“…Our research proved that ES-like cells originated from spermatogonia cells, express high ES-like cells have the same molecular profiling as embryonic stem cells (Mardanpour et al 2008;Kossack et al 2009). …”
Section: Discussionsupporting
confidence: 58%
“…[9][10][11]25,26 These cells have been confirmed to be pluripotent and possess ES cell characteristics as demonstrated by alkaline phosphatase staining, SSEA1 expression, chimera assay, differentiation into somatic cells of the three germ layers in vitro and teratoma formation in vivo.…”
Section: Discussionmentioning
confidence: 96%
“…Although some ES cell lines can be adapted for permanent expansion on gelatine, 32 gPS cells are preferentially cultured on MEF to keep their capacity of continuous proliferation and to stabilize their undifferentiated state. [9][10][11]25,26 Proliferation rate of gPS cells on Resomer LR704 was lower than that of gPS cells on MEF. However, this polymer supported the typical ES cell-like morphology and stable expression of Oct4-GFP fluorescence over passages.…”
Section: Differentiation Of Germline-derived Pluripotent Stem Cellsmentioning
confidence: 89%
See 1 more Smart Citation
“…However, this commitment may not be as definitive as was initially thought, and some studies suggested that adult stem cells may give rise to specialised cell types of a tissue, other than that from which they originated. [21][22][23][24][25][26] However, the practical use of this sort of phenomena has to be treated with care, as previously reported experiments on this topic in the past 27 have been shown to be non-reproducible. Therefore, adult stem cells are more realistically being proposed as a possible source of material to treat the tissue of origin or closely related tissues.…”
Section: Pluripotent Stem Cell Research: Embryo Destruction Versus Nomentioning
confidence: 99%